Bosnia and Herzegovina : Selected Economic Issues. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Economic Issues paper for Bosnia and Herzegovina reports that output, exports, and incomes have increased and inflation has stabilized. New modern banking laws have been passed in both entities, and the banking sector has been almost completely privatized, with the majority of assets now under foreign ownership. The reforms to the central bank and to the banking system have been aimed to secure stability and to build an efficient financial system.